EVALUATION OF WEB INTERPRETATION ISSUES AND NAVIGATION TECHNIQUES IN FACEBOOK AMONG VISUALLY IMPAIRED USERS - Ramayah, Bavani; Jaafar, Azizah (Malaysian Journal of Computer Science, 2019)
Facebook is an important communication medium among all of us. While Facebook provides an effective way for people to communicate online, it also creates challenges for people with blindness. This causes frustration among visually impaired users who are not able to participate in web interaction. The content arrangement of the Facebook page is the main barrier for Visually Impaired users. Therefore, a detail study is needed to explore the interpretation issue in Facebook. This study aimed to examine visually impaired users’ navigation techniques and the reason of having interpretation issues in Facebook. For the comparison purpose, both observation and analysis were based on visually impaired users’ navigation activities in the desktop version (represents complex layout) and mobile version (represents non-complex layout) of Facebook. Cognitive Walkthrough (CW) and spectrum was used to observe and analyse visually impaired users’ navigation activities during experimental session. This study revealed that visually impaired users overcome their interpretation issues in complex layout by adapting multiple navigation techniques compare to non-complex layout. This study also discovered that information scent has influenced visually impaired users’ navigation method. This become the main cause of web interpretation issues in Facebook since the content arrangement does not consistent with their navigation method.